Pilot Study of Accelerated Low-Frequency Right-Sided Transcranial Magnetic Stimulation for Treatment-Resistant Depression. Issue 3 (September 2016) - Tor, Phern-Chern; Gálvez, Verònica; Goldstein, James; George, Duncan; Loo, Colleen K.
Abstract : Background: Repetitive transcranial magnetic stimulation (rTMS) is an effective option for treatment-resistant depression but requires prolonged repeated daily treatments for 4 to 6 weeks. Pilot studies have showed the possibility of accelerating rTMS safely and efficaciously but thus far only investigated high-frequency left-sided rTMS. We sought to investigate the safety and efficacy of accelerated low-frequency right-sided rTMS. Methods: Our study was an open label accelerated rTMS pilot in 7 treatment-resistant patients (4 unipolar, 3 BP). Accelerated rTMS was given over the right dorsolateral prefrontal cortex at 120% of resting motor threshold at 1 Hz, and 900 pulses were delivered per session. A single rTMS treatment was administered on the first day to test for tolerability, followed by 5 rTMS sessions a day for 2 days, then 7 days of daily rTMS sessions. The total course consisted of 16, 200 pulses across 18 sessions given over 10 consecutive weekdays. The primary outcomes of interest were self- and clinician-rated depression scores (BDI-II and MADRS). Results: All patients successfully and safely completed the accelerated rTMS treatment. MADRS scores decreased significantly by the third day of treatment and BDI II scores by the end of the 10-day treatment. No patients achieved response or remission. Conclusions: Accelerated low-frequency right-sided rTMS was a safe and possibly efficacious treatment for treatment-resistant depression. More research is recommended, including a controlled trial with longer duration of exposure, to establish the efficacy of left- and right-sided accelerated rTMS. Abstract : Pilot study of accelerated low-frequency right-sided transcranial magnetic stimulation for treatment-resistant depression.